(untitled) (IJM: Journal of Multidisiplinary, 2025)
This study aims to analyze the effect of independence, competence, and time budget pressure on audit quality with auditor ethics as a moderating variable. The research employs a quantitative approach using primary data obtained through questionnaires distributed to auditors working at Public Accounting Firms (KAP) in Bekasi City. The variables examined in this study include audit quality as the dependent variable, independence, competence, and time budget pressure as independent variables, and auditor ethics as the moderating variable. The sampling technique used was purposive sampling, resulting in 56 respondents who met the research criteria. Data analysis was conducted using SmartPLS 3.0 software to test the relationships among variables both simultaneously and partially. The results indicate that independence and competence have no significant effect on audit quality, while time budget pressure has a positive and significant effect on audit quality. These findings suggest that time pressure can encourage auditors to perform their work more efficiently within the bounds of professional standards. The moderating test results reveal that auditor ethics do not strengthen or weaken the relationships between independence, competence, and time budget pressure on audit quality.